2017
DOI: 10.1248/bpb.b17-00531
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Expression of a Single-Chain Variable Fragment (scFv) Antibody against Ganoderic Acid A: A Cost-Effective Approach for Quantitative Analysis Using the scFv-Based Enzyme-Linked Immunosorbent Assay

Abstract: Due to the highly specific binding between an antibody and its target, superior analytical performances was obtained by immunoassays for phytochemical analysis over conventional chromatographic techniques. Here, we describe a simple method for producing a functional single-chain variable fragment (scFv) antibody against ganoderic acid A (GAA), a pharmacologically active metabolite from Ganoderma lingzhi. The Escherichia coli BL21(DE3) strain produced a large amount of anti-GAA scFv. However, in vitro refolding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…is study used synthetic immunogen to obtain antiganoderic acid A antibodies in the immune serum of experimental rabbits. An indirect competitive ELISA with good specificity and sensitivity for the detection of ganoderic acid A was constructed using synthetic coating antigen and antiganoderic acid A antibody, compared with the high-performance liquid chromatography adopted by Hongling Dong, Duanping Lu, and others [24,25], compared with the liquid chromatography-tandem mass spectrometry adopted by Liangqin Liu and Yongli Liu [26,27], and compared with the enzyme-linked immunosorbent assay method constructed by Sakamoto Seiichi, Gorawit Yusakul, and others [28][29][30]. In comparison, this method has a lower detection limit.…”
Section: Discussionmentioning
confidence: 99%
“…is study used synthetic immunogen to obtain antiganoderic acid A antibodies in the immune serum of experimental rabbits. An indirect competitive ELISA with good specificity and sensitivity for the detection of ganoderic acid A was constructed using synthetic coating antigen and antiganoderic acid A antibody, compared with the high-performance liquid chromatography adopted by Hongling Dong, Duanping Lu, and others [24,25], compared with the liquid chromatography-tandem mass spectrometry adopted by Liangqin Liu and Yongli Liu [26,27], and compared with the enzyme-linked immunosorbent assay method constructed by Sakamoto Seiichi, Gorawit Yusakul, and others [28][29][30]. In comparison, this method has a lower detection limit.…”
Section: Discussionmentioning
confidence: 99%
“…DNA template was resverse transcribed by total RNA that derived from hperimmune positive mice spleen after inoculation inactivated EMCV‐PV21 as antigen. Yusakul et al reported that they used SOE‐PCR producing a functional scFv antibody against ganoderic acid A (GAA), a pharmacologically active metabolite from Ganoderm lingzhi . Although the orientation of VH‐link‐VL or the VL‐linker‐VH can express functional scFv, the prokaryote expression of VL‐linker‐VH scFv is 20 times higher than in the opposite direction scFv .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Rosetta (or Transetta) hosts supplemented with tRNAs of four E. coli rare codons are also candidates that can be used to improve the low expression levels of scFv to some extent (Sharma et al., 2014; Wang, Dong, et al., 2016). Certain engineered strains, such as CyDisCo (Gaciarz & Ruddock, 2017) and Shuffle (Ismail et al., 2015; Yusakul et al., 2017) also play a role in maintaining the formation of disulfide bonds in scFv (Kang & Seong, 2020).…”
Section: Screening Of Scfv Using Phage Display Technologymentioning
confidence: 99%